2015
DOI: 10.1186/s12859-015-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Field phenotyping of grapevine growth using dense stereo reconstruction

Abstract: BackgroundThe demand for high-throughput and objective phenotyping in plant research has been increasing during the last years due to large experimental sites. Sensor-based, non-invasive and automated processes are needed to overcome the phenotypic bottleneck, which limits data volumes on account of manual evaluations. A major challenge for sensor-based phenotyping in vineyards is the distinction between the grapevine in the foreground and the field in the background – this is especially the case for red-green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
0
33
0
2
Order By: Relevance
“…Two monochrome images and one RGB image per vine (MCS) were captured with real background. The two monochrome images were rectified in a pre‐processing step as described by Klodt et al (). The rectified images had parallel epipolar lines that allowed for efficient computation of depth maps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two monochrome images and one RGB image per vine (MCS) were captured with real background. The two monochrome images were rectified in a pre‐processing step as described by Klodt et al (). The rectified images had parallel epipolar lines that allowed for efficient computation of depth maps.…”
Section: Methodsmentioning
confidence: 99%
“…Surface areas were computed using the dense depth reconstruction for all points in the foreground class (Figure ). The complete method is described by Klodt et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paulus et al [20], [21] showed a feature based histogram analysis method to classify different organs in wheat, grapevine and barley plants. A segmentation algorithm to monitor grapevine growth was presented by Klodt et al [22]. A similar type of work on plant organ segmentation by unsupervised clustering was proposed by Wahabzada et al [23].…”
Section: Related Workmentioning
confidence: 97%
“…The disadvantage of using remote sensing technologies is the high costs that are required. More recently, authors have proposed using digital imaging and computer vision techniques using cheaper ground-based cameras [22]. The work by Rodríguez-Pulido et al [23] described a characterization of grape seeds and grape berries by digital image analysis and showed that the development of the grape could be visually determined by tracing its changes in size and color.…”
Section: Related Workmentioning
confidence: 99%